2023
DOI: 10.3389/fnhum.2022.1074033
|View full text |Cite
|
Sign up to set email alerts
|

The experience of sensorimotor integration of a lower limb sensory neuroprosthesis: A qualitative case study

Abstract: IntroductionLower limb prosthesis users often struggle to navigate uneven terrain or ambulate in low light conditions where it can be challenging to rely on visual cues for balance and walking. Sensory feedback about foot-floor interactions may allow users to reduce reliance on secondary sensory cues and improve confidence and speed when navigating difficult terrain. Our group has developed a Sensory Neuroprosthesis (SNP) to restore sensation to people with lower limb amputation by pairing electrical stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…LLA01 received the surgically implanted SNP seven years prior to the time of this report, with consistent operation and stable sensory responses throughout. The data collection for this study lasted for approximately five months, during which time participants routinely visited our laboratory for other experiments following their implant surgery (13,15,18,60,61). Throughout this and other previously reported studies, the implanted C-FINEs have demonstrated stable and reliable performance as evidenced by eliciting sensations in consistent locations related to the plantar surface of the foot of the missing limb.…”
Section: Discussionmentioning
confidence: 94%
“…LLA01 received the surgically implanted SNP seven years prior to the time of this report, with consistent operation and stable sensory responses throughout. The data collection for this study lasted for approximately five months, during which time participants routinely visited our laboratory for other experiments following their implant surgery (13,15,18,60,61). Throughout this and other previously reported studies, the implanted C-FINEs have demonstrated stable and reliable performance as evidenced by eliciting sensations in consistent locations related to the plantar surface of the foot of the missing limb.…”
Section: Discussionmentioning
confidence: 94%
“…LLA01 received the surgically implanted SNP 7 years before the time of this report, with consistent operation and stable sensory responses throughout. The data collection for this study lasted for approximately 5 months, during which time participants routinely visited our laboratory for other experiments after their implant surgery ( 13 , 15 , 18 , 60 , 61 ). Throughout this and other previously reported studies, the implanted composite flat interface nerve cuff electrodes (C-FINEs) have demonstrated stable and reliable performance, as evidenced by eliciting sensations in consistent locations related to the plantar surface of the foot of the missing limb.…”
Section: Discussionmentioning
confidence: 99%
“…Among the highest priority needs desired by individuals with lower limb loss are to improve their ability to walk safely, to move around more independently, and to integrate back into the community without feeling excluded ( Manz et al, 2022 ). Lack of sensory feedback from a missing foot could contribute to the observed deficits in gait stability and lower confidence in prosthesis use ( Kim et al, 2023 ; Schmitt et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%